Systematic analysis on the obtaining of fibrinolytic fungi enzymes (Research, Society and Development, 2022)
Fibrinolytic proteases operate directly on fibrin clot and are able to maintain blood flow. Fungi show up as viable sources for obtaining this enzyme. The purpose of this systematic review is to is to unveil all the information concerning production, purification and characterization of fibrinolytic proteases by fungi. The search was conducted in ScienceDirect, PubMed and Scopus databases, using as keywords “(Fibrinolytic enzyme) OR (Fibrinolytic protease) AND (Fungal or Fungus or Fungi)”. Delimiting period of 10 years (2011-2021). The results obtained were filtered by selection criteria, and review articles or articles outside the scope of this work were excluded. The articles were evaluated and scored (0-10) according to pre-established criteria. None of the studies obtained the score 10, however the study with the highest score (9) presented relevant data in all criteria analyzed, obtaining fibrinolytic enzyme from Xylaria curta. Among the 21 selected articles, 12 different genera appear and Submerged Fermentation and purification of Serino-proteases were more described. This work also observed a greater representation of purification and characterization steps, indicating the need for attention to cultivation process and enzymatic application. It is clear that the production of these enzymes by fungi is pertinent towards the high recovery observed even after purification and its tendency for pharmaceutical application.